پاکستان کے سیاسی نظام میں عدم استحکام کا جائزہ :سیرت النبیﷺ کی روشنی میں : Analysis of instability in Pakistan's political system: In the light of Sirat ul-Nabi - Hafiz Muhammad Waseem Yaseen; Muhammad Noor; Hafiz Muhammad Kashif (Al Manhal Research Journal, 2023)
The establishment of the state of Madinah, which was initially only for the formation of a society, was in fact the result of the Prophet's 13 years of training. Which shows that for an organized and civilized society, moral education and training of individuals and self-purification is a basic need. Both of these characteristics are used for the stability of the state. If we look at the current situation, the boundaries of government have become so wide that many areas of life cannot survive without being directly or indirectly affected by government decisions. At this time, the power of government has become the biggest factor in changing the system and values of the society. Pakistan's political situation is currently going through dangerous stages. All boundaries have been crossed to gain power. Due to unfamiliarity with Islamic politics, the political situation has deteriorated so much that political stability has been lost. The main objective of this research paper is that Political stability in Pakistan is a very important aspect without it man cannot progress in any field of life. In order to achieve political stability, it is necessary to first understand Islamic politics, for which this article will describe the Qur'an and Hadith and the sayings of various personalities. And in this article, some of the principles of the Prophet (peace and blessings of Allah be upon him) will be mentioned which will bring stability in politics. Qualitative research technique was used for the collection and analysis of data.